REKOGNISI ASPEK-ASPEK PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - siti fatimah Siti Fatimah; Zurriat Nyndia Rahmawati (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The interpretation of this study applies an analytic-did active approach in the study based on qualitative descriptive standards. The understanding of text and context studies in content uses observation, then data is detected based on textual techniques from data from past study documents. An appropriate curriculum is needed to translate the internalization of Indonesian for foreign speakers. Multi-method engineering in multi-variation based on the objectives and characteristics of language skills with local culture fundamentals has become the standard for efforts to develop Indonesian by increasing the richness of the vocabulary, the standardization of the language system, language tunings, and increasing the functioning of Indonesian as an international language. BIPA learners psychologically need an interaction model in the curriculum that can provide interest to accelerate their language repertoire.